2019
DOI: 10.1177/0096144219872767
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of the Masses: Dutch Planners, Local Politics, and the Threat of the Motor Age 1960-1980

Abstract: During the 1950s and 1960s, the Netherlands experienced a rapid growth in car ownership. Dutch planners and politicians soon realized that this growing automobility would radically transform the living environment, daily commute, and consumption behavior of millions of people, in particular of those living in or near large conurbations. By investigating how professional and political elites perceived increasing automobility, and how their responses subsequently affected urban planning in the Netherlands, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
0
0
1
Order By: Relevance
“…Verstrate and Karsten, 2011) and bicycles instead of cars (cf. Verlaan, 2021). Both of these decisions are deeply connected to both the literal and figurative natural climate of the city then and now, as well as the municipality’s current ambition to become an emission-free city by the year 2050 (City of Amsterdam, 2020).…”
Section: Past/present: Temporality and The Urban Environmentmentioning
confidence: 99%
“…Verstrate and Karsten, 2011) and bicycles instead of cars (cf. Verlaan, 2021). Both of these decisions are deeply connected to both the literal and figurative natural climate of the city then and now, as well as the municipality’s current ambition to become an emission-free city by the year 2050 (City of Amsterdam, 2020).…”
Section: Past/present: Temporality and The Urban Environmentmentioning
confidence: 99%
“…In samenhang met cityvorming treedt suburbanisatie op, het proces waarin bewoners gedwongen of vrijwillig buiten de stad gaan wonen terwijl zij hun werkplek in de binnenstad behouden. Hierdoor neemt het woonwerkverkeer toe, en groeit de vraag naar infrastructurele maatregelen, zeker in een tijd van groeiend autobezit (Verlaan 2019a). Hoewel binnensteden reeds sinds het laatste kwart van de negentiende eeuw cityvorming ondergingen (Meurs 2000: 316-321), brachten bestuurders het proces in de jaren vijftig in een stroomversnelling.…”
Section: Markt En Stad In De Naoorlogse Periodeunclassified
“…The growing number of automobiles during the twentieth century led to government policies aimed at redesigning cities for a seamless flow of private cars [1]. As a result, car-centric and car-prioritized transportation planning has long been a policy for many cities and countries worldwide [2,3]. This approach involves expanding the transportation network, such as the construction of new roads, flyovers, underpasses, and widening existing roads to allow cars to constantly flow through cities [4].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of active travel are manifold, such as reduction in financial losses due to reduced congestion, reduction in greenhouse gas emissions and pollution, reduction in road fatalities, improved health, improved equity, social cohesion, and perceptions of security and livability [17,18]. Thus, several countries, such as the Netherlands, developed policies to shift toward active mobility [2]. Several studies have shown that promoting pedestrian-friendly cities requires careful consideration of aspects such as urban design and infrastructure [19].…”
Section: Introductionmentioning
confidence: 99%